Studi Karakteristik dan Faktor-Faktor Downstream User Transportasi Online (Ride Sharing) di Kota Bandung - Rohmat adi prasetyo (Fakultas Ekonomi Universitas Garut, 2018)
Online transportation (ride sharing) is a phenomenon that has developed in the last 5 years. Commonly known as